Ring Transformation of Annulated Benzofuran Derivatives to Medium-Sized Lactones - Fliegel, Lukas; Krauß, Julian; Christoffers, Jens (Synlett, 2023)
Benzannulated eight- and nine-membered-ring lactones were prepared by ring transformation of annulated benzofuran derivatives. The reaction sequence starts with a Brønsted acid catalyzed hydration of the enol ether moiety of the starting materials furnishing hemiacetals as intermediate products which underwent retro-Claisen-type C–C bond cleavage under the reaction conditions. The use of 15 mol% TfOH and two equivalents of water in CHCl3 at 85 °C turned out to be optimal. Products with exocyclic carboxylate function could be further derivatized by amide formation. In total, eleven medium-sized lactones were prepared. Furthermore, three benzannulated spirolactones were obtained from starting materials with exocyclic carboxamide moiety.
Keywords: benzofuran; lactone; medium-sized rings; ring expansion; ring transformation